EFFECTS OF FERMENTATION ON CHEMICAL COMPOSITION AND IN VITRO GAS PRODUCTION OF ALBIZIA LEBBECK PODS - Bawah, J.; Cudjoe, S.; Haruna, F.; Ansah, T. (UDS International Journal of Development, 2023)
The study investigated the effect of fermentation on chemical composition and In vitro gas production of the pod, seed, and seed+husk of Albizia lebbeck. The study consisted of six (6) treatments, which were fermented seed, fermented empty pod, fermented seed+pod, unfermented seed, unfermented empty pod and unfermented seed+pod with each treatment replicated three times in completely randomized design. The fermented test materials were soaked for 3-days and fermented for 2-days with another set soaked for 3-days without fermentation. Dry matter for both fermented and unfermented test material were similar, ranging from 96.0% to 98.2%. Unfermented empty pod had the highest ash content of 8.5% with fermented seed, fermented seed+pod and unfermented seed being similar with mean values of 5.1, 4.6 and 5.1% respectively. Fermented empty pod recorded the highest percentage of NDF and ADF with mean value of 75.1 and 55.7% respectively while fermented seed recorded the least mean values of 25.0% and 10.0% respectively. Fermented seed recorded the highest percentage crude protein of 40.5% with fermented empty pod recording the least of 16.9%. Fermentation had no significant effect on in vitro gas production. Fermentation reduced Metabolizable energy (ME) in seed but did not affect seed+pod and empty pod. Fermentation did not have significant effect on short chain fatty acid in this study. In conclusion, fermentation caused an increase in CP and lower NDF and ADF in the seeds of Albizia lebbeck. Keywords: Fermentation, Albizia Lebbeck, Short Chain Fatty Acid, Seed, Seed+pod